IAP Chemotherapy Regimen Is a Viable and Cost-effective Option in Children and Adolescents With Osteosarcoma: A Comparative Analysis With MAP Regimen on Toxicity and Survival. Issue 4 (11th May 2021) - Verma, Priyanka; Jain, Sandeep; Kapoor, Gauri; Tripathi, Rupal; Sharma, Payal; Doval, Dinesh Chandra
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Cisplatin and doxorubicin are integral components of chemotherapy regimens in the treatment of osteosarcoma. Choice of third agent high-dose methotrexate (HDMTX) or an alkylating agent such as ifosfamide is debatable. The present study compared the impact of MAP (HDMTX-doxorubicin-cisplatin) and IAP (ifosfamide-doxorubicin-cisplatin) chemotherapy regimens on toxicity and survival in children and adolescents with osteosarcoma. Materials and Methods: This was a retrospective study including patients 18 years and younger with osteosarcoma during the study period. Clinical, demographic, chemotherapy regimen, and surgical details and treatment-related toxicity were retrieved from hospital medical records. Prognostic factors affecting overall survival (OS) and event-free survival (EFS) were analyzed. Results: Among 102 patients included in the study, 59 (57.8%) and 43 (42.2%) patients were treated with MAP and IAP regimens, respectively. Two groups were comparable in terms of pretreatment characteristics and surgical treatment. Overall, 95.9% patients underwent limb salvage surgery. There was a statistically increased incidence in supportive care admissions and delay in starting the next cycle of chemotherapy in the MAP group. Among the MAP cohort, the 5-year OS and EFS were 62% and 55% compared with 47% and 44%, respectively, in the IAP cohort ( P =0.143 and 0.316, respectively). On univariate and multivariate analyses, statistically significant factors affecting EFS of the whole group included tumor size, stage, site of metastasis, histologic necrosis, and type of surgery. Conclusions: OS and EFS with both regimens were similar. However, the MAP regimen was associated with a statistically significant increase in incidence of supportive care admissions, delay in next cycle of chemotherapy, and predicted higher cost of treatment.